The effect of selected financial ratios and macroeconomic factors on stock price: A study of Bursa Malaysia Berhad's listed energy companies from 2015 to 2019 - Osida, Rexwin Anthony (Animo Repository, 2022)
This paper analyzes the effects of certain financial ratios and macroeconomic factors on the stock price of listed companies in the energy sector of Bursa Malaysia Berhad. The objectives of the study were as follows: First, to ascertain which financial ratios have an effect on the stock price. Second, to determine which macroeconomic factors have an effect on the stock price. Third, to find out which financial ratios and macroeconomic factors simultaneously have an effect on the stock price. To answer the study’s research questions, the researchers collected the financial data from 16 energy companies listed in Bursa Malaysia Berhad while the macroeconomic data was gathered from Bank Negara Malaysia. From there, model selection was made through the use of lagrange multiplier test, chow test, and hausman test. Followed by classic assumptions, then finally, a regression analysis was then performed on the data. The yielded results were the following: first, current ratio, debt to equity ratio, return on assets, and total assets turnover individually has a significant effect on the stock price. Second, both the inflation rate and exchange rate have a significant effect on the stock price. Lastly, macroeconomic factors and financial ratios simultaneously have an effect on the stock price. Keywords: financial ratios, macroeconomic factors, Bursa Malaysia Berhad